Quality Assessment Of Commercial Sandcrete Hollow Blocks Produced In Kaura District, Abuja - Ibrahim, M.; Yerima, M. A.; Danbuba, Z.; Masud, A. Y.; Ibrahim, M. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Abstart